A The Effectiveness of Islamic Psychospiritual Approach in Mindfulness Program for Developing Teachers' Emotional Intelligence - Syafii, Hisyam; Purnomo, Halim; Syukur, Azam; Azhari, Husain (Program Studi Pendidikan Agama Islam STAI Sayid Mohammad Alawi Al Maliki, 2025)
This study explores the effectiveness of an Islamic psychospiritual approach within mindfulness programs to enhance teachers' emotional intelligence. Through a systematic literature review (SLR) complemented by bibliometric analysis using VOSviewer, this research evaluates 43 selected studies published between 2020 and 2025 that integrate elements such as muraqabah, muhasabah, and tazkiyatun nafs within mindfulness frameworks. Findings indicate that such integration significantly enhances self-awareness, emotion regulation, and empathy, particularly among teachers with high religiosity. Compared to secular-based programs, the Islamic psychospiritual mindfulness approach demonstrated a higher effect size (0.58), better cost-efficiency, and stronger contextual relevance in Muslim communities. The study concludes that this integrated approach provides a spiritually congruent and pedagogically effective model for emotional intelligence development, offering valuable contributions to the fields of educational psychology and Islamic education